Digital Security in Human Security: A Case Study of the Bjorka Hacking Incident - Nadia Varayandita Ingrida; Dody Wibowo (Politicos: Jurnal Politik Dan Pemerintahan, 2024)
The issue of human security in the digital era has garnered attention in line with technological advancements. The threats to individual privacy and security have become increasingly evident, particularly following the hacking incident by Bjorka in September 2022 in Indonesia. This research applies the concept of human security within the context of digital security, highlighting the inequalities in access and vulnerabilities in online privacy. The Bjorka case reflects the complexity of human security, encompassing freedom from fear, freedom from want, and the freedom to live in dignity concerning the fundamental rights of individuals in human security. The aim of this study is to understand the privacy breaches and data hacking conducted by Bjorka and its impact on the human security of Indonesian citizens, especially from the perspective of digital security. This case study research employs interviews with key respondents from diverse backgrounds, who may have been victims of Bjorka's hacking. The study finds that digital security is not only related to technical aspects but also involves disrupted human security issues, pertaining to basic human rights, access limitations, and the gender identity of individuals involved in the digital world.